1997
DOI: 10.30843/nzpp.1997.50.11287
|View full text |Cite
|
Sign up to set email alerts
|

<i>Trichoderma</i> spp. for potential biocontrol of clubroot of vegetable brassicas

Abstract: Twenty-five isolates of Trichoderma spp. were screened against clubroot (Plasmodiophora brassicae) on Chinese cabbage (Brassica chinensis L.)'Wong-Bok' in a glasshouse experiment. Seventeen of the 25 isolates tested significantly reduced disease severity compared to the untreated control. In a subsequent pot trial test with 10 of these isolates, nine significantly increased the top weight of the plant. Field trial results with two isolates (TC45 and TC64) and chitosan (crab shell extract) gave significant redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…Although the benomyl soil-drench (a recommended control method) did not significantly reduce disease severity, it did increase the top weights. Similar results have been observed in a previous trial (Cheah and Page 1997), where benomyl drenches significantly increased yield while providing only marginal disease control. Benomyl has also been reported to stimulate yield in cauliflower crops (Cheah et al 1981).…”
Section: Discussionsupporting
confidence: 90%
“…Although the benomyl soil-drench (a recommended control method) did not significantly reduce disease severity, it did increase the top weights. Similar results have been observed in a previous trial (Cheah and Page 1997), where benomyl drenches significantly increased yield while providing only marginal disease control. Benomyl has also been reported to stimulate yield in cauliflower crops (Cheah et al 1981).…”
Section: Discussionsupporting
confidence: 90%
“…In our laboratory, we found that chitosan concentration increased (750-6000 mg/L), the radial growth of A. alternata, B. cinerea, Colletrotichum gloeosporioides, and Rhizopus stolonifer was decreased [250]. The same effect was reported on Sclerotinia sclerotiorum when chitosan concentrations increased from 1% to 4% [251]. Other studies showed a linear decrease of growth of R. solani as the chitosan concentration gradually increased from 0.5 to 6.0 mg/mL [252].…”
Section: Chitosan and Its Derivatives As Antimicrobial Agents Againstmentioning
confidence: 60%
“…Ruan and Xue [313] showed that rice seed coating with chitosan may accelerate their germination and improve their tolerance to stress conditions. In carrot, seed coating helps restrain further development of Sclerotinia rot [251]. It has also been reported that chitosans can activate plant defense to disease on several other plants such as barley [314], pearl millet [315], carrot [316], sunflower [317], and coconut [318].…”
Section: Chitosan and Its Derivatives In Plant Disease Control (In VImentioning
confidence: 99%
“…One such antagonist with potential to be used as a biocontrol agent is the fungal genus Trichoderma Persoon. Besides being able to protect the cabbage against clubroot-disease caused by Plasmodiophora brassicae, Trichoderma also can control various other diseases caused by fungal pathogens (Cheah and Page 1997;Navi and Bandyopadhyay 2002). Fungal pathogens that have been reported as being controlled to some degree by Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%